Quaker Ways in Foreign Policy - Byrd, Robert, O. (Book collections on Project MUSE., 2014)
For three hundred years the Society of Friends, or Quakers, has been forwarding to governments recommendations on foreign policy. In this study, Dr. Byrd brings together and states carefully and accurately those beliefs, principles, attitudes, and practices which have been fundamental to the Quaker approach.